Silicon Carbide/Polysilazane Composite: Effect of Temperature on the Densification, Phase, and Microstructure Evolution - Fiqhi Fauzi; Alfian Noviyanto; Pipit Fitriani; Amirudin Wibowo; Toto Sudiro; Didik Aryanto; Nurul Taufiqu Rochman (Universitas Gadjah Mada, 2022)
This paper reports a route to suppress the grain growth in silicon carbide (SiC) during its sintering by combining it with polysilazane (PSZ). SiC was mixed with PSZ in a 1:1 weight ratio and sintered at 1600, 1700, and 1800 °C in a hot-pressing furnace. A satisfactory density was obtained at sintering temperatures > 1600 °C. The grain sizes of the SiC/PSZ composites sintered at 1700 and 1800 °C were 112 and 125 nm, respectively. The grain shape of the SiC/PSZ composite sintered at 1700 °C was circular and mainly similar to the initial shape of the SiC powder. Grain shape accommodation was observed at a sintering temperature of 1800 °C. It is suggested that different sample shapes were affected by different liquid phase formations. Silicon oxynitride (Si2N2O) was formed and played an important role in densification and microstructure generation.